Brushless DC motor speed controller for electric motorbike - Adli, Mohd Syakir; Mohamad Hanif, Noor Hazrin Hany; Toha, Siti Fauziah (Institute of Advanced Engineering and Science, 2018)
This paper presents a control scheme for speed control system in brushless dc (BLDC) motor to be utilized for electric motorbike. While conventional motorbikes require engine and fuel, electric motorbikes require DC motor and battery pack in order to be powered up. The limitation with battery pack is that it will need to be recharged after a certain period and distance. As the recharging process is time consuming, a PID controller is designed to maintain the speed of the motor at its optimum state, thus ensuring a longer lasting battery time (until the next charge). The controller is designed to track variations of speed references and stabilizes the output speed accordingly. The simulation results conducted in MATLAB/SIMULINK® shows that the motor, equipped with the PID controller was able to track the reference speed in 7.8x10-2 milliseconds with no overshoot. The result shows optimistic possibility that the proposed controller can be used to maintain the speed of the motor at its optimum speed Keyword